2003
DOI: 10.1016/s0147-6513(02)00030-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17α-ethinylestradiol on sexual development of the amphipod Hyalella azteca

Abstract: The effects of the synthetic estrogen 17alpha-ethinylestradiol (EE) on sexual development of the freshwater amphipod Hyalella azteca was investigated. Organisms were exposed in a multigeneration experiment to EE concentrations ranging from 0.1 to 10 microg/L and the development of both external and internal sexual characteristics were studied. Second-generation male H. azteca exposed from gametogenesis until adulthood to 0.1 and 0.32 microg EE/L developed significantly smaller second gnathopods. The sex ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 28 publications
2
45
2
1
Order By: Relevance
“…Iopromide Groundwater Australia 0.577 [200] Algae S. subspicatus [158] >10.0 g L [201] Iopromide Germany SPE-HPLC-MS/MS SPE-HPLC-MS 40 [202] Iopromide Germany 50 1600 <50 [203] >1.0 g L…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iopromide Groundwater Australia 0.577 [200] Algae S. subspicatus [158] >10.0 g L [201] Iopromide Germany SPE-HPLC-MS/MS SPE-HPLC-MS 40 [202] Iopromide Germany 50 1600 <50 [203] >1.0 g L…”
Section: Discussionmentioning
confidence: 99%
“…Amphib-ians and reptiles exposed to environmental estrogens showed sex reversal as well as significant changes in secondary sex character-istics [156,157]. Concerning invertebrates such as the amphipod Hyalella azteca it was observed that at sub-lethal concentrations of EE2 (0.1-10 µg L −1 ) sexual development of males was affected [158]. On the other hand, the estrogens E2 and EE2 did not show significant effects on reproduction or survival of C. dubia even at concentrations of 1 and 0.5 mg L −1 , respectively [159].…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Morphological and histological changes resulting from exposure to EDs have been documented in fish, amphibians, reptiles, mammals, and arthropods (e.g., Gross et al, 2001;Vandenbergh et al, 2003;Schirling et al, 2006). In mysids, morphology and histology have not been considered widely as a measurable endpoint in toxicological studies.…”
Section: Morphology and Histologymentioning
confidence: 99%
“…An environmental endocrine disrupting chemical (EDC) known as 4-nonylphenol (NP) is suggested to have high estrogenic potency (Noppe et al, 2005), and it is known to interfere with normal vitellogenesis (Ghekierea et al, 2006;Hannas et al, 2011;Ara and Damrongphol, 2012). Generally, estrogen exposure in crustaceans can induce Vtg expression (Atienzar et al, 2002;Vandenbergh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%